Bifidobacterium bifidum FJSWX19M5 alleviated 2, 4, 6-trinitrobenzene sulfonic acid (TNBS)-induced chronic colitis by mitigating gut barrier injury and increasing regulatory T cells. Issue 1 (8th December 2022) - Qu, Dingwu; Yu, Leilei; Tian, Fengwei; Zhang, Hao; Chen, Wei; Gu, Zhennan; Zhai, Qixiao
Abstract : Probiotics have been evaluated as alternative approaches for preventing the relapse of Crohn's disease (CD). Abstract : Probiotics have been evaluated as alternative approaches for preventing the relapse of Crohn's disease (CD). Previously, we observed strain-specific anti-inflammatory properties of Bifidobacterium bifidum in 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) acute colitis models. In this study, we further assessed the effects of several B. bifidum strains on colonic damage, fibrosis, inflammatory factors, intestinal microbial and metabolic profiles, and peripheral regulatory T cells (Tregs) in the context of TNBS chronic colitis in mice. These results indicated that B. bifidum FJSWX19M5, but not FXJWS17M4, ameliorated body weight loss, reduced colonic shortening and injury, decreased markers of gut inflammation, and rebalanced colonic metabolism in TNBS-treated mice. FJSWX19M5 supplementation also promoted Treg cell differentiation and intestinal barrier restoration compared to other strains. All living B. bifidum strains (FJSWX19M5, FXJWS17M4 and FHENJZ3M6) seemed to restore the disruption of the gut microbiota caused by TNBS. The co-culture of B. bifidum strains and mesenteric lymph node cells from TNBS-treated mice showed that those strains with anti-colitis could induce higher IL-10 levels and a lower ratio of IL-22/IL-10 and IL-17/IL-10 when compared to those strains that were not protective. Furthermore, heat-killed FJSWX19M5 exhibited a relief effect on colitis-related symptoms (including body weight loss, colonic shortening and injury). These data imply that specific B. bifidum strains or their lysates may be the current therapeutic alternatives for CD.